2014
DOI: 10.5455/2320-1770.ijrcog20140323
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic and histopathological correlation and evaluation of endometrium in perimenopausal women with abnormal uterine bleeding

Abstract: Long anovulatory periods with unopposed estrogen stimulation may result in endometrial hyperplasia, thus increasing the risk of endometrial cancers. Therefore,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
37
3
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 10 publications
15
37
3
2
Order By: Relevance
“…In present study, analysis of patients according to bleeding pattern the most common bleeding pattern was heavy menstrual bleeding (50%) which was comparable to the study by Pillai SS et al 11 . They had 46.5% patients with menstrual complaints of menorrhagia.…”
Section: Distribution According To Bleeding Patternsupporting
confidence: 77%
“…In present study, analysis of patients according to bleeding pattern the most common bleeding pattern was heavy menstrual bleeding (50%) which was comparable to the study by Pillai SS et al 11 . They had 46.5% patients with menstrual complaints of menorrhagia.…”
Section: Distribution According To Bleeding Patternsupporting
confidence: 77%
“…Shobha S. Pillai et al, 12 reported maximum incidence of fibroid uterus (55.7%) in her study, as an associated clinical finding.…”
Section: Resultsmentioning
confidence: 58%
“…In a similar study of Shobha S. Pillai et al, 12 maximum patients had proliferative phase endometrium and presented with menorrhagia.…”
Section: Resultsmentioning
confidence: 79%
“…Pyari et al 16 found mean endometrial thickness of 17.1 ± 2.10 mm in endometrial hyperplasia, 10.5 ± 2.89 mm in endometrial polyps, 8.76 ± 1.87 mm in the functional endometrium. Pillai et al 17 found that on TVS examination, an endometrial thickness between 5 and 9.9 mm is common. Mean ET was found to be 10.22 ± 3.08 (2-16 mm).…”
Section: Discussionmentioning
confidence: 99%